Therapeutic Applications and Challenges of a Widely Used Antifolate Drug - Rafał Makuch; Alicja Chrościcka; Kamil Gała; Andrzej Czajka; Paweł Lenard; Adam Kucharski; Sara Michalska; Konrad Pilarski; Martyna Dewicka; Alicja Maria Wawrzyniak (Nicolaus Copernicus University in Toruń, 2024)
Introduction and purpose: Methotrexate (MTX) is an antifolate metabolite that interferes with the synthesis and repair of DNA and with cell replication. It has anti-inflammatory and immunomodulatory properties and was first used in 1951 for the treatment of RA and psoriasis. Methotrexate (4-amino-10-methylfolic acid, MTX) is a popular disease-modifying drug for the treatment of rheumatoid arthritis, psoriasis and leukaemia. MTX is an antagonist of folic acid, primarily through inhibition of the proliferative effect. MTX and its metabolites are associated with many serious adverse effects, including gastrointestinal and hepatic toxicity, myelosuppression, stomatitis, etc. Taking methotrexate may contribute to a reduction in the quality of life for patients. Additionally, long-term use of methotrexate requires regular monitoring, which can be burdensome and stressful for patients. In this context, different approaches have been used to improve the therapeutic properties of MTX and to reduce its adverse effects. The long history of the drug has made it possible to assess its efficacy and to collect data on adverse events, including potentially life-threatening adverse events. This article aims to provide a literature-based overview of current knowledge about methotrexate in clinical practice. Materials and Methods: Review and summary of research studies available in open-source format on Google Scholar, PubMed. Conclusion: The result is a picture of methotrexate as a drug that is used for many conditions, but is associated with many side effects that can be a significant problem for patients and healthcare professionals.